Lung function, obesity and physical fitness in young children: The EXAMIN YOUTH study. (November 2019) - Köchli, Sabrina; Endes, Katharina; Bartenstein, Tim; Usemann, Jakob; Schmidt-Trucksäss, Arno; Frey, Urs; Zahner, Lukas; Hanssen, Henner
Abstract: Objective: The prevalence of obesity and physical inactivity in children are increasing globally. The study aimed to investigate the association of obesity and cardiorespiratory fitness (CRF) with patterns of lung function in young children. Methods: In this cross-sectional study, lung function, body mass index (BMI), blood pressure (BP) and CRF (shuttle run stages) were measured in an unselected cohort of 1246 children aged 7.2 ± 0.4 years. All parameters and lung function, such as the ratio of forced expiratory volume in 1 s (FEV1) to forced vital capacity (FVC), were assessed by standardized procedures for children. Statistical models were applied for systematic adjustment of potential confounders. Results: Obese children had significantly higher FEV1 (Coef. (95% CI) (1.57 (1.50; 1.64) L) and FVC (1.75 (1.67; 1.83) L) compared to normal weight children (1.38 (1.37; 1.40) L; (1.53 (1.51; 1.54) L, respectively). However, with each unit increase of BMI, FEV1/FVC decreased (−0.003 (−0.005; -0.001)) due to a disproportional increase in FVC compared to FEV1. Per stage increase of CRF, FEV1 (0.017 (0.008; 0.025) L) and FVC increased (0.022 (0.012; 0.031) L)). In obese children, higher CRF was independently associated with higher FEV1/FVC (0.03 (0.5E-4; 0.06)) due to a higher increase of FEV1 over FVC with increasing fitness. Conclusions: The decrease of FEV1/FVC with increasing BMI suggests that childhood obesity is associated with an imbalance of ventilation and airway flow. In children with obesity, higher CRF is associated with an improved FEV1/FVC ratio. Physical exercise programs may have the potential to improve patterns of lung function in children with obesity.